Functional Finance and the Sustainability of Universal Basic Income - Karl Widerquist (19757040) (2024)
“Functional finance” is an economic theory within the Post Keynesian school of thought. Especially in the form of Modern Monetary Theory (MMT), it has begun to have two big but opposite effects on the debate over Universal Basic Income (UBI). Some people state MMT in an exaggerated way that implies the government can spend all it wants on UBI or anything else without ever raising taxes or borrowing money as if government spending had no limits of any kind. Other people refer to MMT while arguing that any effort to maintain a livable level of UBI is unsustainable. This article discusses the functional finance implications for the cost and sustainability of UBI, arguing that neither of those exaggerated implications are correct. MMT doesn’t free us for the concern for how to support UBI with taxes, but neither does it give reason to believe UBI is any less sustainable. Other Information Published in: Basic Income Studies License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/bis-2023-0024